2020
DOI: 10.3390/plants9121747
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature and Drought-Resilience Traits among Interspecific Chromosome Substitution Lines for Genetic Improvement of Upland Cotton

Abstract: Upland cotton (Gossypium hirsutum L.) growth and development during the pre-and post-flowering stages are susceptible to high temperature and drought. We report the field-based characterization of multiple morpho-physiological and reproductive stress resilience traits in 11 interspecific chromosome substitution (CS) lines isogenic to each other and the inbred G. hirsutum line TM-1. Significant genetic variability was detected (p < 0.001) in multiple traits in CS lines carrying chromosomes and chromosome seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
(178 reference statements)
1
11
0
1
Order By: Relevance
“…The combined effects of drought and heat stresses have been investigated in some field crops such as wheat (Qaseem et al, 2019 ), rice (Costa et al, 2021 ), barley (Zhanassova et al, 2021 ), peanut (Hamidou et al, 2013 ), canola (Elferjani & Soolanayakanahally, 2018 ), sorghum (Johnson et al, 2014 ), and soybean (Cohen et al, 2021 ) at different development stages.The above studies reported that exposure of plants to combined stresses could lead to more acute damage than individual stress. Combined stresses, particularly during the stress‐sensitive reproductive stages, decreased pollen viability (Bheemanahalli et al, 2021 ; Rang et al, 2011 ), gas exchanges (Reddy et al, 2020 ), yield, and quality parameters (Assefa et al, 2018 ) in different crops. Maize is highly sensitive to drought and heat stresses compared with other cereals (Barnabás et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combined effects of drought and heat stresses have been investigated in some field crops such as wheat (Qaseem et al, 2019 ), rice (Costa et al, 2021 ), barley (Zhanassova et al, 2021 ), peanut (Hamidou et al, 2013 ), canola (Elferjani & Soolanayakanahally, 2018 ), sorghum (Johnson et al, 2014 ), and soybean (Cohen et al, 2021 ) at different development stages.The above studies reported that exposure of plants to combined stresses could lead to more acute damage than individual stress. Combined stresses, particularly during the stress‐sensitive reproductive stages, decreased pollen viability (Bheemanahalli et al, 2021 ; Rang et al, 2011 ), gas exchanges (Reddy et al, 2020 ), yield, and quality parameters (Assefa et al, 2018 ) in different crops. Maize is highly sensitive to drought and heat stresses compared with other cereals (Barnabás et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hatta söz konusu melezlemelerin bir sonucu olarak genler arasındaki bağlılık (linkage) durumları göz önüne alındığında dikey gen transferi kavramında adı geçen "gen" ifadesinin boyut değiştirerek daha büyük DNA parçalarını ve hatta bir adım öteye giderek kromozom ya da genom boyutunda meydana gelebilen genetik modifikasyonlara neden olabileceği bilimsel bir gerçektir [24]. Örneğin, klasik ıslah uygulamalarında genom katlanma çalışmaları sonucu oluşturulan allove auto-poliploid bitkiler [25][26][27] ile kromozom ve bu kromozomlar üzerinde yer alan genlerin genom içerisindeki fonksiyonlarının anlaşılmasına yönelik olarak ortaya konan yer değiştirilmiş kendilenmiş hatlar [28][29][30][31] ya da kromozom eliminasyon çalışmaları [32] bu uygulamalara örnek olarak gösterilebilir [33][34][35]. Diğer taraftan melezleme yoluyla sitoplazmik erkek kısır bitkiler geliştirmek amacıyla özellikle polen alıcısı hatlarda yapılan mitokondriyal organel transferlerinin de bu kapsamda değerlendirilmesi gerektiği açıktır [36,37].…”
Section: Bitkilerde Doğal Yollarla Meydana Gelen Dikey Ve Yatay Gen Transferleriunclassified
“…Plant species, and genotypes within species, vary in their sensitivity to temperature ( Munyon et al, 2021 ; Reddy et al, 2021 ). Several studies used variations in morpho-physiological and yield responses to evaluate stress tolerance in oilseed crops: canola ( Elferjani and Soolanayakanahally, 2018 ), peanut ( Arachis hypogaea L.) ( Kakani et al, 2002 ), and cotton ( Gossypium hirsutum ) ( Reddy et al, 2020 ). In addition, to shoot traits, root traits have been used to investigate crop responses to a range of stresses, including drought ( Raju et al, 2014 ), low temperature ( Reddy et al, 2021 ), high temperature ( Alsajri et al, 2019 ), nutrient ( Jia et al, 2022 ), salinity ( Kakar et al, 2019 ), waterlogging ( Walne and Reddy, 2021 ), and UV-B ( Ramamoorthy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%